Implementation of PLTS in Flood Disaster Mitigation System in Pabuaran Village, Kemang district, Bogor Regency: Penerapan PLTS pada Sistem Mitigasi Bencana Banjir di Desa Pabuaran Kec. Kemang Kab. Bogor - Galuh Ika Pratama Putri; Ojak Abdul Rozak; Hafiz Nabil Nurwahid; Hedy Aditya Baskhara; Anto Carmanto (CONSEN: Indonesian Journal of Community Services and Engagement, 2023)
Bogor City has 70% humidity and rainfall is predicted to start in November 2023, so a community service activity was carried out in Pabuaran Village, Kemang Kec. Bogor Regency to make a tool to detect flood disasters (flood mitigation). However, because in Pabuaran Village the distance from the public electricity line from PLN is very far, finally a Solar Power Plant (PLTS) was made using an Off-Grid system to supply flood mitigation tools. By using the implementation method, this PLTS has a power of 100Wp to drive a flood mitigation tool that requires a voltage supply of 12VDC which is accommodated using a battery that has a voltage of 12V. By using PLTS, the implementation of PKM has no obstacles and has been realized according to the fulfillment of system energy supply as the goal.